A cocoa transport, Trinidad - Bryant, Herbert J. (Richardson and Selway Ltd., Trinidad, 2010)
In this picture workers are standing next to donkeys used to transport the cacao beans harvested here to market. The cacao beans are stored for transport in the packs that are strapped to the donkeys' backs.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Donkeys--Trinidad and Tobago; Draft animals--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Agricultural laborers--Trinidad and Tobago